THE INFLUENCE OF KNOWLEDGE ON COMMUNITY PARTICIPATION IN CORAL REEF MANAGEMENT IN TIDUNG ISLAND, SERIBU ISLANDS - Ika Muti Rahmah; Nurul Tri Mutmainah; Ridho Agusman; Eka Putri Handayani; Dio Ramadhani (Universitas Negeri Padang, 2023)
As an archipelagic country, Indonesia is rich with a diversity of coral reef species. This diversity is vulnerable to destruction that can be triggered by human factors or natural factors, including the coral reefs on Tidung Island, the Thousand Islands. This damage can be prevented with the participation of local communities in coral reef ecosystems, who are equipped with knowledge about coral reef management. Therefore, this study is intended to determine the relationship between the level of public knowledge of coral reef management on Tidung Island. This study used quantitative methods with data collection techniques through questionnaires. The results show that the knowledge of the Tidung Island community and management of coral reefs is stated to be valid with an r table of 5% which is 0.361. In the reliability test, a value was obtained (0.646> 0.361), so the questionnaire was declared reliable. In the normality test, the p value sig of all variables is 0.200> 0.005, the residual value is normal. In the linearity test, a value of 72,446 was obtained, then in the hypothesis test, the calculated f value was 28.00> 3.35. Finally, this study concluded that there was a significant influence of the knowledge of the Tidung Island community on coral reef management. Keywords: influence of knowledge; society participation; management; coral reef; Tidung Island